Marketing Agility in the Age of Digital Transformation Industrial Sector Analysis - Prof. Tareq Nael Hashem; Dr. Khalid Atieh (Kurdish Studies, 2024)
The current study aims to analyze the concept of marketing agility in the age of digital transformation (Data-driven decision-making, Automation and personalization, Cross-functional collaboration, and agile methodology) within the Jordanian industrial sector. Quantitative methodology was adopted, and a questionnaire was distributed to a sample of (38) marketing managers within the industrial sector in Jordan. SPSS was employed to process primary data gathered; the results of the study indicated the acceptance of what the study hypothesized, arguing that digital transformation can pave the way for better marketing agility as digital transformation provides marketers with the data, automation tools, cross-functional collaboration opportunity, and agile methodology to respond swiftly and accurately to changing market conditions which helps them adapt more quickly and compete effectively. The study recommended hiring a versatile team with diverse skills can help organizations achieve better marketing agility. Further recommendations were presented in the study.